Avian Influenza Virus Detection by Optimized Peptide Termination on a Boron-Doped Diamond Electrode - Matsubara, Teruhiko; Ujie, Michiko; Yamamoto, Takashi; Einaga, Yasuaki; Daidoji, Tomo; Nakaya, Takaaki; Sato, Toshinori (ACS sensors, 2020)
The development of a simple detection method with high sensitivity is essential for the diagnosis and surveillance of infectious diseases. Previously, we constructed a sensitive biosensor for the detection of pathological human influenza viruses using a boron-doped diamond electrode terminated with a sialyloligosaccharide receptor-mimic peptide that could bind to hemagglutinins involved in viral infection. Circulation of influenza induced by the avian virus in humans has become a major public health concern, and methods for the detection of avian viruses are urgently needed. Here, peptide density and dendrimer generation terminated on the electrode altered the efficiency of viral binding to the electrode surface, thus significantly enhancing charge-transfer resistance measured by electrochemical impedance spectroscopy. The peptide-terminated electrodes exhibited an excellent detection limit of less than one plaque-forming unit of seasonal H1N1 and H3N2 viruses. Furthermore, the improved electrode was detectable for avian viruses isolated from H5N3, H7N1, and H9N2, showing the potential for the detection of all subtypes of influenza A virus, including new subtypes. The peptide-based electrochemical architecture provided a promising approach to biosensors for ultrasensitive detection of pathogenic microorganisms.